2016
DOI: 10.1016/j.fcr.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the causes of variability in crop yields and treatment responses for better tailoring of options for sustainable intensification in southern Mali

Abstract: Options that contribute to sustainable intensification offer an avenue to improve crop yields and farmers' livelihoods. However, insufficient knowledge on the performance of various options in the context of smallholder farm systems impedes local adaptation and adoption. Therefore, together with farmers in southern Mali we tested a range of options for sustainable intensification including intensification of cereal (maize and sorghum) and legume (groundnut, soyabean and cowpea) sole crops and cereallegume inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 44 publications
6
69
3
Order By: Relevance
“…The statistical analysis confirmed farmers' perception and showed that (i) maize, soyabean and groundnut grain yields and maize partial Land Equivalent Ratio (pLER) in intercropping were higher after cotton and maize (the fertilised crops) compared with after sorghum or millet (the un-fertilised crops), (ii) sorghum and soyabean grain yields and cowpea fodder yields were greater on black soils compared with sandy and gravelly soils. Due to pest attacks, cowpea grain yields were not affected by soil type (see Falconnier et al (2016) for more detailed results). As a result, soil type and previous crop defined niches where diversification with legumes without extra input yielded best results (Figure 3).…”
Section: Second Cycle Of Stepmentioning
confidence: 99%
See 4 more Smart Citations
“…The statistical analysis confirmed farmers' perception and showed that (i) maize, soyabean and groundnut grain yields and maize partial Land Equivalent Ratio (pLER) in intercropping were higher after cotton and maize (the fertilised crops) compared with after sorghum or millet (the un-fertilised crops), (ii) sorghum and soyabean grain yields and cowpea fodder yields were greater on black soils compared with sandy and gravelly soils. Due to pest attacks, cowpea grain yields were not affected by soil type (see Falconnier et al (2016) for more detailed results). As a result, soil type and previous crop defined niches where diversification with legumes without extra input yielded best results (Figure 3).…”
Section: Second Cycle Of Stepmentioning
confidence: 99%
“…Access to subsidised fertiliser for cotton and maize is guaranteed by the Compagnie Malienne pour le Développement des Textiles (CMDT), and the nutrients carried-over benefit the following crops (Falconnier et al, 2016;Ripoche et al, 2015). This carry-over is the backbone of the niches identified for maize/cowpea intercropping and soyabean production ( Figure 3) (Falconnier et al, 2016).…”
Section: Farm Reconfiguration For Sustainable Intensification?mentioning
confidence: 99%
See 3 more Smart Citations